الجرائم المرتكبة عبر وسائل الاعلام من منظور الشريعة الإسلامية دراسة مقارنة بالقانون الوضعي - عثمان, ئاراس حمه أمين; كريم, فاروق عبدالله (Sulaimani Journal for Humanities, 2021)
Media Crimes are considered as a crime expressions, in Islamic Law (Shariah) view point. This type of crime affects Community members through Spoken, Written, or Presented Images and so on by Involving the Modern Media Channels which are, indeed, Useful tools and elements that if the users Utilize them for the Benefits of Communities, Particularly in the Framework of Freedom of Opinion and Expression. So, the Role of Media, Nowadays, Should be Bases on the two Main Points that are Acknowledged in the Islamic Shariah and the International Laws. The First one is Freedom of Opinion and Expression and the Second is Protecting the Interests of Individuals and Community, Based on Shariah Law.